Video Game Therapy for Emotional Regulation and Impulsivity Control in a Series of Treated Cases with Bulimia Nervosa. (20th September 2013) - Fagundo, Ana B.; Santamaría, Juan J.; Forcano, Laura; Giner‐Bartolomé, Cristina; Jiménez‐Murcia, Susana; Sánchez, Isabel; Granero, Roser; Ben‐Moussa, Maher; Magnenat‐Thalmann, Nadia; Konstantas, Dimitri; Lam, Tony; Lucas, Mikkel; et al.
Abstract: Although standard psychological treatments have been successful in treating several core features in eating disorders (ED), other characteristics such as emotional regulation or impulsivity appear to be more resistant to change. There is a growing body of evidence to support the efficacy of cognitive remediation for cognitive and emotional difficulties in ED. Playmancer/ Islands is a video game (VG) designed to specifically treat mental disorders, characterized by problems in impulse control. The objective of the game is to increase self‐control over emotions, decision making and behaviours. The aim of this study is to describe the results from a consecutive series of nine bulimia nervosa patients who were treated with the VG in addition to cognitive behaviour therapy (CBT). The outcomes included clinical and psychopathological questionnaires, and physiological measures were obtained during the VG. Emotional regulation improved, heart rate variability increased, and respiratory rate and impulsivity measures reduced after the treatment. These findings suggest that VG training may enhance treatment for ED. Copyright © 2013 John Wiley & Sons, Ltd and Eating Disorders Association.